Evolutionary Analysis of MBW Function by Phenotypic Rescue in Arabidopsis thaliana - Zhang, Bipei; Hülskamp, Martin (Frontiers in Plant Science, 2019)
The MBW complex consisting of the three proteins R2R3MYB, bHLH and WDR regulates five traits in A. thaliana including trichome and root hair patterning, seed coat color, anthocyanidin production and seed coat mucilage release. The WDR gene TTG1 regulates each trait in specific combinations with different bHLH and R2R3MYB proteins. In this study we analyze to what extent the biochemical properties of the MBW proteins contribute to trait specificity by expressing them in appropriate Arabidopsis thaliana mutants. We show that the rescue behavior of A. thaliana bHLH and R2R3MYB protein is sufficient to explain the function as derived previously from mutant analysis. When extending this rescue approach using MBW proteins from other species we find that proteins involved in anthocyanidin regulation typically show a rescue of the anthocyanidin phenotype but not of the other traits. Finally, we correlate the rescue abilities of MBW protein from different species with the A. thaliana proteins.